STRAIN-STRESS DISTRIBUTION OF BRACED NODE OF FRAMED MULTI-STOREY WOODEN HOUSE (Collection of scientific works «Modern structures of metal and wood», 2020)
Framed multi-storey wooden residential construction is developing very rapidly in many countries around the world. The use of wooden infill beams made of wooden glued beams and OSB (oriental strand board) increases the efficiency of design solutions. Especial difficult in the design  and  manufacture  of  beam  structures  in  multi-storey  framed  houses  are  the  beam-column joints, which can be hinged or supple. Preferably, these nodes are considered supple, which ensures the spatial operation of the frame and reduces its deformability against the hinges. As a rule, nodes are executed with steel elements which connect beams to columns by means of bolts and nails. The following  constructive  decision  of  a  frame  node  is  offered:  a  rectangular  glued  column  and  a crossbar  in  the  form  of  an  I-beam  with  an  OSB-wall  and  regiments  from  a  bar  strengthened  by glued  wood  in  supporting  zones.  Support  zones  of  crossbars  are  made  of  continuous  rectangular section of a glued bar. For support of crossbars on a column the head with projecting beams from sheet  steel  up  to  4  mm  thick,  with  apertures  for  fastening  is  put  on.  The  overhanging  length corresponds  to the  width  of  the  support  zones  of the  crossbars.  After  fixing  the  crossbars  to the projecting beam, the support area of he column of the upper floor is connected to the upper shelf of the crossbars with a fastening element in the form of a corner. The wall of the projecting beam is attached to the column, the projecting beam shelf is attached to the bottom shelf of the beam. The vertical walls of the projecting beam on both sides are attached to the wall of the support zone of the beam. To analyze the stress-strain distribution of the I-beam in the software complex "LIRA-SAPR" was developed a spatial computer model of the node. The stress-strain distribution of the beam was analyzed by the fields of displacements and stresses, as well as by the deformations of the  structure.  The  research  results  allow  us  to  conclude  about  the  structural  reliability  of  the proposed node solution.